Perspectivas teóricas e pragmáticas da arquivologia e seus impactos na preservação da memória social - Oliveira, Danielle Alves de (2023)
Archivology has a long history as an empirical activity, however, its outline as an autonomous scientific discipline began in the 19th century after the publication of numerous manuals and the emergence of professional courses. Therefore, despite the relevance of the publications for the theoretical conception of the area, it is clear that Archivology cannot detach itself from the technical model essentially focused on practice. Aiming at a more solid apparatus for scientific reflections, some researchers include Archivology in the framework of Information Science, however, fundamental questions in the area remain unanswered. In this way, the present research arises from the need to re-dimension the reflections of the field, with a view to deepening its theory and practice, thus making it possible to re-signify its technicist model that conditions and stiffens professional practices and naturalizes the idea of memory without privileging the its aspects as a social construction. We are aware that the State and other existing power structures use political strategies to meet their needs and encourage silencing and manipulation of our collective memory, however, this scenario can only be modified if we launch effective reflections around the discourses that structure theoretical and pragmatic perspectives and delimit norms and routines in the archival scope. Therefore, in view of this context, we have as a general objective: to present and problematize the discursive processes that structure the theoretical and pragmatic perspectives that define norms and routines in the archival scope and their impacts on the preservation of social memory. Methodologically, we used exploratory-explanatory research with a qualitative nature. As for the technical procedures, we will make use of bibliographical research, in which we will follow the stages of identification, systematization and critical analysis of the bibliographical production on the theme pertinent to the field of investigation of Archivology. After analyzing the literature, we reaffirm the need to expand research focused on the area, and, above all, for a more critical and propositional training of archivists so that it is possible to recognize the different discourses around the norms and routines of the archival scope, mainly, in terms of evaluation. This process is still very attached to the discourses of History, and fundamentally linked to the demands of the State. In this way, the idea of memory in Archivology is treated in a natural way and without privileging this substrate as a social construction, resulting in permanent collections that do not represent society in its multiple dimensions, thus hindering the process of re-signification of memory. Finally, we reaffirm that for archives to effectively contribute to society, it is essential that archivists attend to the evaluation process, respecting not only the functional value of documents, but also their informational, cultural and memory potential.